2022
DOI: 10.1038/s41598-022-14393-6
|View full text |Cite
|
Sign up to set email alerts
|

Infant birth weight estimation and low birth weight classification in United Arab Emirates using machine learning algorithms

Abstract: Accurate prediction of a newborn’s birth weight (BW) is a crucial determinant to evaluate the newborn’s health and safety. Infants with low BW (LBW) are at a higher risk of serious short- and long-term health outcomes. Over the past decade, machine learning (ML) techniques have shown a successful breakthrough in the field of medical diagnostics. Various automated systems have been proposed that use maternal features for LBW prediction. However, each proposed system uses different maternal features for LBW clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Different classification approaches for LBW have been utilized in several studies. In the United Arab Emirates, Khan et al [ 20 ] assessed the performance of several ML algorithms. Through 5-fold cross-validation, they showed that the RF approach was superior to alternatives in birth weight estimation with regard to mean absolute error (294.53 g).…”
Section: Discussionmentioning
confidence: 99%
“…Different classification approaches for LBW have been utilized in several studies. In the United Arab Emirates, Khan et al [ 20 ] assessed the performance of several ML algorithms. Through 5-fold cross-validation, they showed that the RF approach was superior to alternatives in birth weight estimation with regard to mean absolute error (294.53 g).…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight is stratified into low birth weight, normal birth weight and high birth weight if the baby weighs 2500grammes (g), 2500–3999 g and ≥4000 g, respectively 21 22…”
Section: Methodsmentioning
confidence: 99%
“…Their high accuracy and low area under the receiver operating characteristic curve (AUROC) scores revealed that misleading performance remains a persistent issue [33]. The third group comprises studies that used data rebalancing techniques for their imbalanced data sets [30][31][32]. However, these studies only applied a single data rebalancing method to multiple ML models, either oversampling [30] or SMOTE [31,32].…”
Section: Related Workmentioning
confidence: 99%